Tvorjenke s pomenom nosilnika lastnosti v novejšem slovenskem besedju (na primeru NSL in SNB) - Voršič, Ines (Slavia Centralis, 2020)
DERIVATIVES WITH MEANING OF NOMEN ATTIBUTIVUM IN LATER SLOVENE VOCABULARY (EXAMPLES: NSI AND SNB) Fierce economic, political, and cultural processes at the turn of the millennium have brought substantial linguistic changes to the Slovenian situations in everyday language use. The new language phenomena emerge at all linguistic levels; the dynamics of development are most evident in the feld of lexis. The article discusses neologisms with the meaning of carrier properties from the affx-morpheme and semantic perspective and it represents current typical affxes of mentioned semantic group.